Antimicrobial resistance profile and multidrug resistance patterns of Streptococcus pneumoniae isolates from patients suspected of pneumococcal infections in Ethiopia - Bekele Sharew; Feleke Moges; Gizachew Yismaw; Wondwossen Abebe; Surafal Fentaw; Didrik Vestrheim; Belay Tessema (BMC, 2021)
Abstract Background Antimicrobial-resistant strains of Streptococcus pneumoniae have become one of the greatest challenges to global public health today and inappropriate use of antibiotics and high level of antibiotic use is probably the main factor driving the emergence of resistance worldwide. The aim of this study is, therefore, to assess the antimicrobial resistance profiles and multidrug resistance patterns of S. pneumoniae isolates from patients suspected of pneumococcal infections in Ethiopia. Methods A hospital-based prospective study was conducted from January 2018 to December 2019 at Addis Ababa city and Amhara National Region State Referral Hospitals. Antimicrobial resistance tests were performed from isolates of S. pneumoniae that were collected from pediatric and adult patients. Samples (cerebrospinal fluid, blood, sputum, eye discharge, ear discharge, and pleural and peritoneal fluids) from all collection sites were initially cultured on 5% sheep blood agar plates and incubated overnight at 37 °C in a 5% CO2 atmosphere. Streptococcus pneumoniae was identified and confirmed by typical colony morphology, alpha-hemolysis, Gram staining, optochin susceptibility, and bile solubility test. Drug resistance testing was performed using the E-test method according to recommendations of the Clinical and Laboratory Standards Institute. Results Of the 57 isolates, 17.5% were fully resistant to penicillin. The corresponding value for both cefotaxime and ceftriaxone was 1.8%. Resistance rates to erythromycin, clindamycin, tetracycline, chloramphenicol and trimethoprim-sulfamethoxazole were 59.6%, 17.5%, 38.6%, 17.5 and 24.6%, respectively. Multidrug resistance (MDR) was seen in 33.3% isolates. The most common pattern was co-resistance to penicillin, erythromycin, clindamycin, and tetracycline. Conclusions Most S. pneumoniae isolates were susceptible to ceftriaxone and cefotaxime. Penicillin has been used as a drug of choice for treating S. pneumoniae infection. However, antimicrobial resistance including multidrug resistance was observed to several commonly used antibiotics including penicillin. Hence, it is important to periodically monitor the antimicrobial resistance patterns to select empirical treatments for better management of pneumococcal infection.